Ability and Effort Attributions: Do They Affect How Managers Communicate Performance Feedback Information? - Dugan, Kathleen Watson (Academy of Management Journal, 1989)
Patterns of performance feedback communication were studied using laboratory simulations. The data indicate that a consistent relational communication pattern, or script, was associated with feedback sessions on poor performance. However, managers' initial attributions of effort or ability as the reason for subordinates' poor performance influenced how they defined their role within the script and thereby controlled the flow of interaction. The nature of the control patterns dyad members used was related to the degree of change in initial attributions, salary decisions, and performance assessments.